First record of multiple nests of yellow-spotted river turtle (Podocnemis unifilis) in a nest of black caiman (Melanosuchus niger) in Amazonia - Maffei, Fábio; da Silveira, Ronis (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
This communication reports the first record of communal egg-laying of yellow-spotted river turtle (Podocnemis unifilis) in a nest of the black caiman (Melanosuchus niger). This event was recorded in a flooded savannah in the municipality of Oiapoque, northern Amapá state, Brazilian Amazonia. Inside the nest of M. niger we founded 182 eggs of P. unifilis divided into eight clutches.